2013
DOI: 10.5005/jp-journals-10024-1414
|View full text |Cite
|
Sign up to set email alerts
|

Compare the Efficacy of Two Commercially Available Mouthrinses in reducing Viable Bacterial Count in Dental Aerosol produced during Ultrasonic Scaling when used as a Preprocedural Rinse

Abstract: The aerolization of oral microbes occurring during dental procedures can potentially result in cross-contamination in the dental operatory and transmission of infectious agents to both dental professionals and patient. It is reasonable to assume therefore, that any stratagem for reducing the viable bacterial content of these aerosols could lower the risk of cross-contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 6 publications
3
16
0
9
Order By: Relevance
“…Study reported by Yadav et al reported that CHX 0.2% was highly effective in inhibiting sub gingival plaque formation and hence prevents development of gingivitis [18]. In accordance with our study, Shamila et al reported that Chlorhexidine mouthwash was more effective than herbal mouth rinse in reducing microbial load of aerosols [25].…”
Section: Table 1 Comparison Of Cfu Count Mean Standard Deviation Ansupporting
confidence: 91%
“…Study reported by Yadav et al reported that CHX 0.2% was highly effective in inhibiting sub gingival plaque formation and hence prevents development of gingivitis [18]. In accordance with our study, Shamila et al reported that Chlorhexidine mouthwash was more effective than herbal mouth rinse in reducing microbial load of aerosols [25].…”
Section: Table 1 Comparison Of Cfu Count Mean Standard Deviation Ansupporting
confidence: 91%
“…From this result, can be stated that the farther distance from reference point (patient's oral cavity) then the less of bacterial aerosol quantity. It is in line with a research conducted by Logothethis and Martinez 20 showed that the number of cfus decrease with increasing the distance from the reference point. Nevertheless, the result of group I was not in line with group II.…”
Section: Resultssupporting
confidence: 92%
“…Shetty et al 20 about the efficacy of pre-procedural mouth rinses (chlorhexidine gluconate and tea tree oil) in reducing microbial content of aerosol product during ultrasonic scaling procedures by viable bacterial count. The results showed that all the antiseptic mouthwash significantly reduced the bacterial cfus.…”
Section: Resultsmentioning
confidence: 99%
“…Razão da exclusão dos estudos (n = 08) Retamal Valdez et al, Gupta et al,2014Shetty et al,2013Feres et al,2010Dawson et al,2016Klyn et al,2001Logothetis, Martinez-Welles 1995Monserrate, 1970 Não apresentaram dados da UFC antes do uso de enxaguatórios bucais.…”
Section: Registros Removidos Após Duplicatasunclassified
“…No total, 367 indivíduos foram incluídos. Na maioria dos estudos, o dispositivo gerador de aerossol foi o aparelho ultrassônico (Retamal-Valdes et al, 2017, Gupta et al, 2014, Shetty et al, 2013, Feres et al, 2010, Klyn et al, 2001, Fine et al, 1993aestudo 1, Fine et al, 1993aestudo 2, Fine et al, 1993be Fine et al, 1992. Nos demais estudos, os aerossóis foram gerados por baixa rotação para polimento de superfícies dentárias (Logothetis;Martinez-Welles, 1995), caneta de alta rotação para preparo de cavidades dentárias (Mohammed;Monserrate, 1970) e caneta de baixa rotação para remoção de aparelhos ortodônticos (Dawson et al, 2016).…”
Section: Características Dos Estudosunclassified